Staff Competence, Support Services, and VAT Collection Performance: Does Managerial Performance Mediate the Relationship? - Fakhari, Nabil Yousuf Mohammad; Din, Badariah Hj; Omar, Rusdi (South Asian Journal of Social Sciences and Humanities, 2022)
VAT collection is a major issue for several governments around the world. Different countries  have applied different techniques to enhance VAT collection. Likewise, the UAE government has  introduced VAT and its collection is challenging for them. One of the key issues that has been  observed in the literature is that support services are limited, and the staff appointed for collection  is incompetent and require proper training. Similarly, the managerial role at the same time cannot  be ignored. Therefore, the purpose of the study is to identify the mediating role of managerial  performance between staff competence, support services and VAT collection performance. For the  said purpose, primary quantitative causal research has been conducted using adopted  questionnaires. The findings of the study are based on structural equation modeling technique and  contributed to Economic Theory of Tax Compliance by identifying the mediating role of  managerial performance. The study is equally important for the practitioners in understanding the  importance of boosting staff competence and provision of support services for enhancing VAT  collection.
Keywords: Staff competence; support services; managerial performance; VAT collection